Missouri Community, Public Health, and Primary Care Linkage: 2011–2012 Pilot Project Results & Evaluation - Yun, Shumei (Mo Med, 2015)
This pilot project worked to establish linkages among community-based organizations, health care providers, and public health systems. The partnerships were created to help ensure identification, referral, and follow-up for community members with uncontrolled high blood pressure or pre-hypertension to lay the groundwork for sustainable referral and health education support systems in rural communities. The evaluation shows the project helped some participants control their blood pressure and change their blood pressure management behaviors.